El patrimonio técnico, una herramienta clave en el sector bancario ecuatoriano para la verificación de la solvencia económica. - Castro Cruz, Miriam Yacqueline (2017)
The development of the implementation of banking regulation and supervision was due to the financial crises that have occurred in recent years in the developed countries of the world and in the countries of Latin America, which was sufficient reason for the International Monetary Fund and the Bank World Bank to discuss the new restructuring of financial reforms in which central banks were concerned to opt for emerging measures to control the security of the financial system, as proposed by the Basel Committee on Banking Supervision in most countries in the world have implemented this Method of supervision and banking regulation, it should be noted that in each country they have adopted this method according to their financial regulation. The objective of the present investigation is to determine that the Banking Sector in Ecuador is complying with the macroprudential policies of the legislation and laws of Ecuadorian legislation, the adoption of the international standards demanded by the banking supervision committee and Basle where it is established The capital requirements, which reflects the financial solvency index, the technical capital seeks to measure the economic solvency of banking entities.The present research work has the following structure, the analysis of the countries of Latin America regarding the implementation of the measures established by the Basel Committee on capital requirements in the banking sector, the risk of markets in the sector Economic, political and financial crises that framed the history of Ecuador and emerging measures that was established on the financial regulations for the security and control of the economic solvency of financial institutions. This topic focuses mainly on private banking, the transparency and solvency that banks should have to assume financial risks, the importance of the analysis of the technical heritage to maintain the solvency patrimonial. The collection of information is extracted explicitly from scientific journals, documents and sites of different web portals that refer to laws and financial regulations, which allow the development of our work, for the process of data collection is investigated in the page Of the portal of the website of the Superintendency of Banks to carry out the analysis of the economic solvency in the banking sector to achieve the purposes proposed for our investigation. The results obtained through the investigation allow to determine the comparative and financial analysis of two banking entities to verify the financial regulations that it considers to the technical patrimony as fundamental factor for the solvency patrimonial.The collection of information is extracted explicitly from scientific journals, documents and sites of different web portals that refer to laws and financial regulations, which allow the development of our work, for the process of data collection is investigated in the page Of the portal of the website of the Superintendency of Banks to carry out the analysis of the economic solvency in the banking sector to achieve the purposes proposed for our investigation. The results obtained through the investigation allow to determine the comparative and financial analysis of two banking entities to verify the financial regulations that it considers to the technical patrimony as fundamental factor for the solvency patrimonial. According to the analysis, the characteristics of supervision and regulation in Ecuador, despite the great changes that have occurred over the years and facing financial problems of the past, our economy is restored thanks to the advances of financial investment. The technical heritage is an interesting and very important issue for banks because it allows us to know about the ability to take risks against the financial obligations of a changing economy to protect user deposits.